First record of Scapholeberis freyi Dumont and Pensaert, 1983 (Crustacea:Anomopoda: Daphniidae) from Colombia - Fuentes-Reinés, Juan M. (2021)
From the analysis of plankton samples from a temporary pond of northern Colombia some female specimen of the daphinid cladoceran Scapholeberis freyi Dumont and Pensaert, 1983 was collected. It represents the first report in Colombia and expands its known occurrence in South America. The specimens observed are described and compared with available morphological data of their closest congeners. A brief descriptions of this taxon based on Colombian material is given.